Human resource accounting disclosure among listed companies in Vietnam: An empirical study - Duc Hieu Pham; Thi Huyen Chu; Thi Bich Ngoc Hoang; Thi Thu Thuy Lai (Cogent Business & Management, 2022)
This study examines the association between corporate attributes and human resource accounting disclosures of non-financial companies listed on the Vietnam Stock Exchange. Data were obtained from the annual reports of 80 selected companies for the period 2016-2018. Content analysis was also applied to analyze the extent of human resource disclosures. To determine the level of voluntary disclosures of Vietnamese listed companies, the human resource disclosure index consisting of 32 items was developed. For hypothesis testing, we used panel regression, employing techniques like the pooled-ordinary least squares, fixed effects model, and random effects model to analyze the data. The findings reveal a significant positive relationship among firm size, foreign ownership, and human resource accounting disclosures. However, other variables, including listing age, leverage, and profitability, exhibit no relationship with human resource accounting disclosures. In addition, based on the content analysis results, it can be concluded that human resource accounting disclosures by Vietnamese listed companies are quite low, and there is room for improvement. The study contributes to the limited research on this field in Vietnam. Moreover, the disclosure index constructed in this study may be utilized by local companies as a benchmark to enhance their human resource disclosures in the future.
Keywords: M40; M41; 650; Corporate disclosures; Human resource accounting; human resource accounting disclosures; Vietnam; Vietnam Stock Exchange